Analysis of Roof Displacement in Steel Structures with and without Panel Zone (International Journal of Architecture and Urbanism, 2024)
The purpose of this study is to determine how panel zones influence the seismic behavior of steel structures in Medan City, utilizing the Indonesian earthquake zone standards SNI 1726:2019 and focused on seismic design category D. The structures are designed with the special moment-resisting frame (SMRF) system, which has a seismic significance factor of 4 and soft soils. The study examines the roof displacement and story drift ratio of a 7-story steel structure with and without panel zones subjected to seismic loads. The results show that the building with panel zones has a roof displacement that is approximately 9.23% higher in the X direction and 10.41% higher in the Y direction than the structure without panel zones. Similarly, the story drift ratio for the structure with panel zones is 9.21% greater in the X direction and 11.55% greater in the Y direction than the structure without panel zones. These findings indicate that incorporating panel zones changes a rigid structure into a semi-rigid one, allowing more rotational movement at the beam-column joints, thereby improving the building's flexibility and overall earthquake resistance.